PENGARUH ENVIROMENTAL, SOCIAL DAN GOVERNANCE DISCLOSURE TERHADAP PROFITABILITAS PADA PERUSAHAAN CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) 2021-2023 - Hardiansyah, Ahmad Rifky; Merina, Citra Indah (ITB AAS Indonesia Surakarta, 2024)
This research was conducted with the aim of testing and analyzing the effect of environmental, social, and corporate governance disclosure on profitability. This study is a type of quantitative descriptive research using secondary data. The population that is the focus of this study is consumer non-cyclical companies listed on the Indonesia Stock Exchange during the period 2021-2023. The sampling method for this study was carried out using purposive sampling. The criteria for selecting research samples include consumer non-cyclical companies listed on the stock exchange from 2021-2023, consumer non-cyclical companies that are not included in the food and beverage sector, companies that do not publish annual financial reports from 2021-2023, companies that do not have sustainability reports from 2021-2023. The number of consumer non-cyclical companies that meet these criteria and are the research sample is 18 companies. Data collection was carried out by downloading financial reports and sustainability reports from the Indonesia Stock Exchange website. The analysis technique used is multiple linear regression. The results of the study indicate that environmental and social disclosure partially does not affect profitability, while governance disclosure affects profitability